PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, DAN LEVERAGE TERHADAP NILAI PERUSAHAAN (Studi Empiris: Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2013 – 2016) - Siti Nurlaela, Eva Selviana Kurniawati, Kartika Hendra Titisari & (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2018)
This study aims to determine whether there is a partial influence Profitability, Company Size and Laverage to Company Value. The population in this study is a banking company listed on the Indonesia Stock Exchange (IDX) that has been audited and continuously publish financial statements for five periods. Technique of sampling this research use purposive sampling, hence obtained sample of research counted 31 company for every year, so that data obtained as 124 observation data. Data analysis technique is done by descriptive statistic test, classical assumption, hypothesis testing with multiple linear regression analysis. The result of research stated that partially profitability variables do not have an effect on company value while firm size and leverage variable influence to company value. Keywords: company value, profitability, company size, leverage